Auxiliary Words in Uzbek Language (Eurasian Research Bulletin, 2023)
Noun, pronouns and predicate words, action name and comes after adjectives and expresses their relation to other words auxiliary words are helpers. For example: Xadicha xola Baxrobod qishlog’ida kichik o’g’li Obidjon bilan turar edi.Sen uchun kitob olib keldim..They are similar to agreements according to the function of auxiliaries. Sometimes assistants comes in the same function as the conjunctions, and one is used instead of the other. For example: qo’l bilan ko’tardim. I picked it up by hand (means of a tool). Jahonda dong’imiz paxta orqali. (Gafur Ghulam.) In the world, our grain is made of cotton (means or causal meaning). Maktab uchun mebel olindi. Furniture was bought for the school (namely meaning). But agreeing with an assistant is not something. This is in the following example see also: Paxta uchun kurash - for the unions of the struggle for cotton the auxiliary cannot be replaced by the suffix -ga